2019
DOI: 10.1186/s12974-019-1647-5
|View full text |Cite
|
Sign up to set email alerts
|

HSV-1 triggers paracrine fibroblast growth factor response from cortical brain cells via immediate-early protein ICP0

Abstract: BackgroundHerpes simplex virus-1 (HSV-1) infections of the central nervous system (CNS) can result in HSV-1 encephalitis (HSE) which is characterized by severe brain damage and long-term disabilities. Different cell types including neurons and astrocytes become infected in the course of an HSE which leads to an activation of glial cells. Activated glial cells change their neurotrophic factor profile and modulate inflammation and repair. The superfamily of fibroblast growth factors (FGFs) is one of the largest … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 78 publications
0
29
0
Order By: Relevance
“…To address the possible involvement of different CNS cell types as well as their interaction, we developed a protocol to investigate the proteome and the secretome of mixed primary cultures from the brain cortices of neonatal C57BL/6J mice ( Figure 1A ). As previously established and characterized ( 29 ), we dissected the cortices, and cultured the cells for six days to obtain an ex vivo system which contains the major CNS-cell types ( Figures 1B–J ). The cells were inoculated with HSV-1 for 20 h prior to processing the samples for cell proteome analyses.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…To address the possible involvement of different CNS cell types as well as their interaction, we developed a protocol to investigate the proteome and the secretome of mixed primary cultures from the brain cortices of neonatal C57BL/6J mice ( Figure 1A ). As previously established and characterized ( 29 ), we dissected the cortices, and cultured the cells for six days to obtain an ex vivo system which contains the major CNS-cell types ( Figures 1B–J ). The cells were inoculated with HSV-1 for 20 h prior to processing the samples for cell proteome analyses.…”
Section: Resultsmentioning
confidence: 99%
“…HSV-1 infects neurons, astrocytes, and oligodendrocytes in HSE-patients, mice, and human and murine primary cortical cultures (26)(27)(28)(29)33). Moreover, HSV-1 infection modulates the physiology of other cell types such as oligodendrocytes and microglia, the resident "macrophages" of the brain (27).…”
Section: Hsv-1 Infects Primary Cortical Brain Cellsmentioning
confidence: 99%
See 2 more Smart Citations
“…The HSV-1 gB gene copy number was clearly reduced as shown by qPCR, suggesting that the HCFC1R1 deficiency affects HSV-1 propagation (Figure 6A). To further ask if loss of HCFC1R1 was correlated with the life cycle of HSV-1, we analyzed the mRNA expression of several viral genes including ICP0 (representing immediate early gene), TK (early gene), and GD (late gene) in the control and BGC-823 HCFC1R1−/− cells by qRT-PCR in 24, 48, and 72 hours after infection (2527). qRT-PCR data showed that missing HCFC1R1 significantly inhibited the mRNA transcription in BGC-823 HCFC1R1−/− cells at the various time points (Figure 6B, C, D).…”
Section: Resultsmentioning
confidence: 99%